Pararenalfat Tissue: Rate of Pararenal Obesity and Relation with Anthropometric Indices of Obesity - V. I. Podzolkov; A. E. Bragina; K. K. Osadchiy; J. N. Rodionova; D. A. Bayutina (Столичная издательская компания, 2022)
Aim. To study a rate of excessive pararenal fat tissue (PRFT) thickness and its relationship with anthropometric obesity indices.Material and methods. 372 patients (152 men and 220 women) were included in the study, the average age was 63.5±13.3 years. There were measured: height, weight, waist circumference (WC), hip circumference (HC), body mass index (BMI), WC/height ratio, sagittal abdominal diameter (SAD), body fat percentage (BFP), body surface area (BSA), body adiposity index (BAI) and visceral obesity index (VAI). All subjects underwent abdominal multispiral computed tomography. PRFT thickness was detected on a single slice at the level of the left renal vein.Results. 27% of the examined group had BMI<25 kg/m2, 28% - excessive body mass, 45% - obesity. The median PRFT thickness was 1.61 (1.03; 2.46) cm. There were correlations between PRFT thickness and glucose (r=0,64, p<0,05) and uric acid (r=0,46, p<0,05) levels. The threshold of referential PRFT thickness was 1,91cm. The rate of pararenal obesity was 9,9% among those with normal body mass, 29,3% in excessive body mass, 66,1% - in 1 class obesity, 67,7% - in 2 class, and 90,1% - in 3 class. The correlation analysis revealed a significant positive correlation between the PRFT thickness and obesity indices with exception of VAI and BAI: with BMI (r=0.43, p<0.05), WC (r=0.57, p<0.05), SAD (r=0.58, p<0.05), BFP (r=0.48, p<0.05), WC/height ratio (r=0.46, p<0.05), and BSA (r=0.58, p<0.05).Conclusion. Excessive PRFT may be detected isolated without any external anthropometric signs of obesity, wherein it is an active component of metabolic disorders typical for obesity. The most significant indices for the detection of pararenal obesity may be WC, SAD, and BSA.